Trans-cinnamaldehyde-Biosurfactant Complex as a Potent Agent against Enterococcus faecalis Biofilms - Mingxin Hu; Shanthini Kalimuthu; Chengfei Zhang; Islam A. A. Ali; Prasanna Neelakantan (MDPI AG, 2022)
Enterococcus faecalis is an opportunistic microbial pathogen frequently associated with diverse infections, including those of the skin and teeth, as well as those from surgical wounds. It forms robust biofilms that are highly tolerant to most antimicrobials and first-line antibiotics. Therefore, investigating alternative strategies to eradicate its biofilms is a critical need. We recently demonstrated that trans-cinnamaldehyde (TC) potently kills E. faecalis biofilm cells and prevents biofilm recovery, and yet, the extreme hydrophobicity of TC hampers clinical translation. Here, we report that a complex of TC with an FDA-approved biosurfactant (acidic sophorolipid/ASL) significantly reduces the bacterial viability and biomass of E. faecalis biofilms, compared to TC alone. A confocal laser-scanning microscopic analysis demonstrated that the TC-ASL treatment significantly decreased the biofilm thickness and volume. In conclusion, our study highlights the anti-biofilm potential of the newly developed TC-ASL.